Novel HPMA Copolymer-Bound Constructs for Combined Tumor and Mitochondrial Targeting - Cuchelkar, Vaikunth (2008)
A wide variety of therapeutic agents may benefit by specifically directing them to the mitochondria in tumor cells. The current work aimed to design delivery systems that would enable a combination of tumor and mitochondrial targeting for such therapeutic entities. To this end, novel HPMA copolymer-based delivery systems that employ triphenylphosphonium (TPP) ions as mitochondriotropic agents were developed. Constructs were initially synthesized with fluorescent labels substituting for drug and were used for validation experiments. Microinjection and incubation experiments performed using these fluorescently labeled constructs confirmed the mitochondrial targeting ability. Subsequently, HPMA copolymer–drug conjugates were synthesized using a photosensitizer mesochlorin e(6) (Mce(6)). Mitochondrial targeting of HPMA copolymer-bound Mce(6) enhanced cytotoxicity as compared to nontargeted HPMA copolymer–Mce(6) conjugates. Minor modifications may be required to adapt the current design and allow for tumor site-specific mitochondrial targeting of other therapeutic agents.